Incomplete endoscopic resection of colorectal polyps: a prospective quality assurance study - Pedersen, Ina B.; Bretthauer, Michael; Kalager, Mette; Løberg, Magnus; Hoff, Geir; Matapour, Senaria; Hugin, Silje; Frigstad, Svein O.; Seip, Birgitte; Kleist, Britta A.; Løvdal, Leif; Botteri, Edoardo; Holme, Øyvind (Endoscopy, 2020)
Background Endoscopic screening with polypectomy has been shown to reduce colorectal cancer incidence in randomized trials. Incomplete polyp removal and subsequent development of post-colonoscopy cancers may attenuate the effect of screening. This study aimed to quantify the extent of incomplete polyp removal.Methods We included patients aged 50–75 years with nonpedunculated polyps ≥ 5 mm removed during colonoscopy at four hospitals in Norway. To evaluate completeness of polyp removal, biopsies from the resection margins were obtained after polypectomy. Logistic regression models were fitted to identify factors explaining incomplete resection.Results 246 patients with 339 polyps underwent polypectomy between January 2015 and June 2017. A total of 12 polyps were excluded due to biopsy electrocautery damage, and 327 polyps in 246 patients (mean age 67 years [range 42–83]; 52 % male) were included in the analysis. Overall, 54 polyps (15.9 %) in 54 patients were incompletely resected. Histological diagnosis of the polyp (sessile serrated lesions vs. adenoma, odds ratio [OR] 10.9, 95 % confidence interval [CI] 3.9–30.1) and polyp location (proximal vs. distal colon, OR 2.8, 95 %CI 1.0–7.7) were independent risk factors for incomplete removal of polyps 5–19 mm. Board-certified endoscopists were not associated with lower rates of incomplete resection compared with trainees (14.0 % vs. 14.2 %), OR 1.0 (95 %CI 0.5–2.1). Conclusion Incomplete polyp resection was frequent after polypectomy in routine clinical practice. Serrated histology and proximal location were independent risk factors for incomplete resection. The performance of board-certified gastroenterologists was not superior to that of trainees.